The microenvironment in myeloma. Issue 2 (March 2020) - Lomas, Oliver C.; Tahri, Sabrin; Ghobrial, Irene M.
Abstract : Purpose of review: The aim of the review is to describe recent advances in our understanding of how multiple myeloma interacts with its cellular and molecular neighbours in the bone marrow microenvironment, and how this may provide targets for prognostication and prevention. Recent findings: The bone marrow microenvironment in myeloma is beginning to yield targets that are amenable to therapy. A number of trials demonstrate some clinical efficacy in heavily pretreated disease. The challenge remains for how and when these therapeutic interventions are of particular benefit early in disease progression. Summary: Multiple myeloma is rarely curable and its interactions with the bone marrow microenvironment are evident. However, separating cause from effect remains a challenge. We propose that targeting specific niches within the bone marrow will yield therapies that have the potential for significant benefit in myeloma and may facilitate earlier intervention to disrupt an environment that is permissive for myeloma progression.